Phaeorrhiza (Physciaceae), a new lichen genus record to China - Zhong, Qiuyi; Zhang, Yanyun; Wang, Xinyu; Timdal, Einar; Gong, Hede; Wang, Zizhi; Wang, Lisong (Phytotaxa, 2021)
The genus Phaeorrhiza is reported as new for the Chinese lichen biota, including the two species, Phaeorrhiza nimbosa (Fr.) H. Mayrhofer & Poelt and P. sareptana var. sphaerocarpa. (Tr. Fr.) H. Mayrhofer & Poelt. The genus grows on soil in alpine meadows, morphologically characterized by a squamulose to subfoliose thallus, rhizohyphae, and Beltraminia-type ascospores. P. nimbosa has cryptolecanorine to eulecanorine apothecia, while P. sareptana var. sphaerocarpa has lecideine apothecia. Descriptions, a key and a phylogram of these species are provided.